Scent-sational Strategies: Boosting Refill Perfume Brand Image through Product, Price, Service, and Social Media - Sujono, Hernandi; Hurriyati, Ratih; Wibowo, Lili Adi; Hendrayati, Heny (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
Brand image remains pivotal in contemporary marketing discourse, particularly within niche industries. This study advances brand theory by empirically examining how product attributes, pricing strategies, service quality, and social media engagement collectively shape the brand image of refill perfumes through customer experience mediation. Employing Structural Equation Modeling–Partial Least Squares (SEM-PLS) via SmartPLS, data from 332 refill perfume customers across five cities in West Java, Indonesia were analyzed using cluster sampling. Findings indicate that all examined factors significantly enhance brand image, with customer experience acting as a crucial mediator. Practically, this suggests that refill perfume businesses can strategically leverage product quality, competitive pricing, superior service, and dynamic social media presence to cultivate a robust brand identity.